The Potential Role of Small States and their „Niche Diplomacy” at the UN and in the Field of Human Rights, with Special Attention to Montenegro - Lakatos, István (Pécs journal of international and European law, 2017)
The study examines the different approached followed by small states in order to represent their national interests and make them visible in the international arena. The author underlines the comparative advantages of small states, which can make these countries very efficient, active and successful players in the field of multilateral human rights diplomacy. The fundamental precondition of playing this role is the strong political determination of the given government to the cause of human rights and the presence of several highly qualified and courageous diplomats who are willing to take the risk to be involved in sensitive human rights negotiations and able to resist political pressure coming from bigger states as a result of their activism. Montenegro was a classic example of this state, which placed the protection of human rights in the heart of their foreign policy aiming at EU and NATO membership.